An Analysis of Public Relations Management of IAIN Curup Bengkulu in Improving Digital Information Systems - Irwan Fathurrochman; Eka Ariskawanti; Sedya Santosa (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
The study was carried out to analyze public relations management at IAIN Curup Bengkulu in improving digital information systems; this topic is critical to discuss because it is to know the progress of educational institutions following the challenges of education 4.0. The type of research applied is descriptive qualitative, with the support of literature and news that shows the facts that occur in the field. Data collection was carried out using interviews, documentation, and observation. So from this technique, the researchers found data that aligned with the research topic. Public relations in tertiary institutions is a supporting wheel for quality progress in the education system. This is seen through his authority to establish connections with the community to various partners who follow the contribution of improvement in the quality of education. Public Relations of IAIN Curup Bengkulu in following the digital information system can be seen from the publication activities carried out through the Website, Youtube, and Social Media Applications. In addition, public relations efforts to improve the image of the institution can also be determined from activities: campus branding, agency marketing, and increasing cooperation networks with various partners. Digital branding needs to be improved by the public relations department of IAIN Curup Bengkulu to support the digital marketing program. Improvements must be considered, including providing media and more engaging content to prospective students. The study results show that the public relations service system at IAIN Curup Bengkulu has so far been beneficial in providing information and implementing educational marketing. The targeted information system is also primarily implemented via the internet. So this category shows that public relations activities have effectively moved information systems.